A Spectral Estimation Theory for Color Appearance Matching - Jiang, Haomiao; Farrell, Joyce; Wandell, Brian (Electronic Imaging, 2016)
There are several reports describing color vision in subjects who are dichromatic in one eye and trichromatic in the other. Formulae fit to the between-eye color appearance matches in such unilateral dichromats have been used to predict color appearance for dichromats [1][2]. In this paper, we describe a general principle, spectral estimation theory, that guides how to predict the mapping from two cone class absorptions in a dichromatic eye to three cone class absorptions in a trichromatic eye. The theory predicts matches by first estimating the smoothest, non-negative, spectral power distribution that is consistent with the measured cone absorption rates (e.g., of a dichromat). We then use this spectral estimate to calculate the absorption rate for the missing cone type (the standard color observer). In addition to predicting color appearance of dichromats, the theory predicts color appearance matches between color anomalous subjects and the standard color observer. Finally, the theory offers guidance about the possible effects on color appearance of gene therapy treatment for colorblindness.